El Impuesto a la Renta peruano y los gastos deducibles para los contribuyentes con renta de quinta categoría - Llave Angulo, Irvin Luis (2018)
Objective: To analyze the violation of the principle of contributory capacity present in the Deductible Expenses of Income Tax for the fifth category income taxpayers of dependent workers, period 2017. Method: It is an explanatory, quantitative and non-experimental research based on quantitative analysis. Results: In the determination of Taxable Income there is a fixed deduction equivalent to 7 UIT (Taxation Unit) and an additional deductible expense equivalent to 3 UIT. This result compared with the real contributory capacity is represented by the cost of a family's basic needs of dependent workers according to their family size shows that the tax that a worker without family would pay with a salary of 3500, 00 soles is much lower than the amount that this worker would have to pay consistent with his real economic capacity, and as the family load increases, the tax payable would be less than that of a worker without a family burden. Conclusions: The income tax of fifth category taxes all the income of the dependent employees allowing a blind deduction of 7 UIT with an additional of 3 UIT of their gross income without considering the economic and personal situation (family burden) that each worker with respect to revenue received and all expenditure incurred; thereby transgressing the principle of his contributory capacity by not considering all expenses.